THE EFFECT OF LAYERED CURRICULUM MODEL ON STUDENTS’ ACADEMIC ACHIEVEMENT AND ATTITUDES IN ENGLISH COURSE - ORAKCI, Åženol (MOJES: Malaysian Online Journal of Educational Sciences, 2019)
The aim of this study is to examine the LCM (layered curriculum model) on students’ achievements, and attitudes in English course and to determine their opinions about the LCM. In order to achieve these aims, mixed method was employed. The study lasted for five weeks and was conducted in one of the Anatolian High Schools in Ankara, Turkey in 2016-2017’s academic year. The study was conducted on an experimental group composed of 31 ninth grade students and control group composed of 32 ninth grade students. The experimental group was lectured with the LCM whereas the control group was lectured with a teaching process in which current curriculum prescribed by Ministry of National Education (MoNE) was followed. Research data were gathered through the academic achievement test, the scale of attitude towards English lesson and semi-structured interview form. The study results revealed that the LCM implementation in the experimental group increased students’ academic achievement and attitude more significantly than the experimental group. The students interviewed in the experimental group expressed that the LCM promoted their cognitive and affective developments, their language skills, facilitated their learning process, made their learning permanent, developed their motivation, self-confidence, responsibility, decision making skills and abilities. They also stated that the activities in the LCM were fun, interesting, and instructional.